Staging and Wintering Areas of Snow Geese Nesting on Howe Island, Alaska - Johnson, Stephen R. (ARCTIC, 1996)
From July 1980 to July 1990, leg bands were put on 4556 adults, subadults, and goslings from the lesser snow goose (Chen caerulescens caerulescens) colony (~1000 nesting birds) on Howe Island, near Prudhoe Bay, Alaska. In addition, 1431 neck bands were put on 1714 of the leg-banded adults and subadults. During the period from September 1980 through May 1991, 3244 discrete, within-year resightings and recoveries were received of neck-banded and leg-banded birds during fall, winter, early spring, and late spring. During mid to late August each year, the Howe Island geese migrated eastward from the Prudhoe Bay area to staging/feeding areas in the Arctic National Wildlife Refuge, Alaska and in adjacent areas of the Yukon Territory. In mid to late September they moved southward down the Mackenzie Valley. Cluster analyses for the ten-year period 1980-90 revealed six separate distribution loci for the geese during the fall, with the largest proportion (84.7%) in one location in southeastern Alberta and southwestern Saskatchewan. Analyses revealed 11 separate distribution loci for the geese during winter from 1980 to 1991; the largest proportion (79.2%) was in northern California and southern Oregon. There were seven different distribution loci for the geese during early spring from 1981 to 1991; the largest proportion was in northern California and southeastern Oregon (81.4%). There were five distinct aggregations of the Howe Island geese during late spring from 1981 to 1991, with the largest proportion (79.1%) in staging/feeding areas in Montana, Alberta, and Saskatchewan. Most geese in both flyways were faithful to specific overwintering locations from one year to the next. Of 262 birds for which year-to-year data were available, 98% in the Pacific Flyway returned to the same region in subsequent winters, and 90% in the Central Flyway returned to the same region. Nevertheless, some geese from both flyways moved to the other flyway during subsequent winters, and a few moved from the Pacific to the Central Flyway ...